Cost-effectiveness of the adjuvanted quadrivalent influenza vaccine for older adults in South Korea - Youngji Song; Eunha Shim (Human Vaccines & Immunotherapeutics)
South Korea’s National Immunization Program administers the quadrivalent influenza vaccine (QIV) to manage seasonal influenza, with a particular focus on the elderly. After reviewing the safety and immune response triggered by the adjuvanted QIV (aQIV) in individuals aged 65 and older, the Ministry of Food and Drug Safety in Korea approved its use. However, the extensive impact of aQIV on public health is yet to be fully understood. This study assessed the cost-effectiveness of replacing QIV with aQIV in South Korean adults aged 65 years and older. A dynamic transmission model, calibrated with national influenza data, was applied to compare the influence of aQIV and QIV on older adults and the broader population throughout a single influenza season. This study considered both the direct and indirect effects of vaccination on the elderly. We derived the incremental cost-effectiveness ratios (ICERs) from quality-adjusted life-years (QALYs) and costs incurred, validated through a probabilistic sensitivity analysis with 5,000 simulations. Findings suggest that transitioning to aQIV from QIV in the elderly would be cost-effective, particularly if aQIV’s efficacy reaches or exceeds 56.1%. With an ICER of $29,267/QALY, considerably lower than the $34,998/QALY willingness-to-pay threshold, aQIV presents as a cost-effective option. Thus, implementing aQIV with at least 56.1% efficacy is beneficial from both financial and public health perspectives in mitigating seasonal influenza in South Korea.